Tinjauan terhadap Kewenangan Peradilan Agama dalam Penyelesaian Sengketa Perbankan Syariah di Indonesia - Besse Suci Nurul Maqfira; Ana Kurnia; Amirul Syam Fadhil; Ilham Ilham (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
The development of the sharia economy in Indonesia demands the existence of a judicial institution capable of resolving disputes in accordance with Islamic legal principles. The Religious Court, through the amendment of Law Number 3 of 2006, has obtained the authority to handle cases in the field of sharia economics, including Islamic banking disputes. However, the implementation of this authority faces various challenges, both in terms of regulation, dualism of authority with general courts, and institutional readiness, such as human resources and infrastructure. This study employs a qualitative method with a normative juridical approach to analyze the legal basis, court practices, and institutional responses in the exercise of this authority. The results of the study indicate that the Religious Court holds great potential as a pillar for upholding sharia economic law but requires reinforcement in various aspects, including improving judges’ competencies, digitalizing the judicial system, and fostering inter-institutional synergy. Moreover, legal protection for justice seekers highly depends on the effectiveness and professionalism of the judicial institution. Therefore, a sustainable strategy is needed to build the institutional capacity of the Religious Court to respond to the dynamics of the sharia economy in a fair, accountable manner and in line with Islamic legal values in Indonesia.